Critical conditions for brittle-ductile removal transition in nano-ZrO2 dental ceramic grinding. (1st January 2012) - Li, C.H.; Liu, Z.R.; Hou, Y.L.; Ding, Y.C.
This study was aimed at the theoretical analysis and experimental investigation on the critical conditions for the brittle-ductile removal transition in nano-ZrO2 dental ceramic grinding. The K-P36 numerical-control precision surface grinder was employed for the grinding test on 3Y-TZP nano-ZrO2 dental ceramics. The experimental results indicated that the maximal thickness of the undeformed chipping smaller than 1.9 μm corresponded to the ductile removal mode; the brittle-fracture removal induced by side cracks appeared when the maximal thickness of undeformed chipping was between 1.9 μm and 2.1 μm, and the removal mode was brittle-ductile mixed removal; when the maximal thickness of undeformed chipping was 5.23 μm, large-scale brittle fracture appeared at the grinding surface, and a large number of pits induced by the brittle fracture in half-coin shape remained on the surface. It was deduced that the maximal thickness of undeformed chipping was the decisive factor that determined the brittle-ductile removal transition in nano-ZrO2 grinding.